Executive incentives under common ownership - Schneider, Thomas (Journal of Corporate Finance, 2025)
Relative performance evaluation (RPE) increases competition and limits pay-for-luck by rewarding executives for outperforming rivals. This study tests whether institutional investors reduce RPE use when they own stakes in competing firms. Contrary to this, the Big Three asset managers – BlackRock, Vanguard, and State Street – demonstrate strong preferences for RPE, reflected in portfolio firms’ RPE adoptions, say-on-pay vote support, and peer group selections. No evidence suggests that common ownership by these or other institutional investors reduces RPE, as confidence bounds and point estimates are near zero. Overall, the rising prevalence of RPE challenges concerns about anticompetitive effects from common ownership.